The Influence of Ownership Structure, Sales Growth, and Business Risk on The Firm Value of Transportation and Logistics Companies - Ni Nyoman Karina Indraswari; Anak Agung Gde Putu Widanaputra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Firm value is a metric that reflects investors’ perception of management’s success in managing the company, as represented by the market price of its shares. The transportation and logistics sector in Indonesia has faced significant challenges, especially since the COVID-19 pandemic, which has led to fluctuations in firm value. This study aims to analyze the effect of managerial ownership structure, sales growth, and business risk on the firm value of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. This research employs a quantitative approach with an associative research design. The primary theoretical framework used is agency theory, which explains the relationship between owners and managers and highlights the importance of aligning their interests in decision-making processes. The sample consists of 16 companies selected using purposive sampling, resulting in 48 observations over three years. Data were obtained from the official IDX website and analyzed using multiple linear regression with the help of SPSS software. The dependent variable is firm value, measured by price to book value (PBV), while the independent variables are ownership structure, measured by management ownership percentage (MOP); sales growth, measured by growth sales rate (G); and business risk, measured by the degree of operating leverage (DOL). The results of the study indicate that all three independent variables have a positive and significant effect on firm value. These findings support agency theory and demonstrate that an appropriate ownership structure, stable sales growth, and effective management of business risk can enhance firm value. This study is expected to contribute to the development of accounting science and managerial practices in the transportation and logistics sector, as well as provide insights for investors in making informed investment decisions.